2023
DOI: 10.20319/pijtel.2023.71.0114
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Tolerance in Indonesia: A Study on the Ministry of Education Youtube Channel

Abstract: This article investigates the maxim of tolerance based on the inspirators' opinion on tolerance which is stated clearly in each video related to Kant's moral theory and ways of teaching implemented by each inspirator in promoting tolerance. This research applies a qualitative approach. The data is taken by observing 4 videos, based on the number of views that contain tolerance, of the Ministry of Education and Culture of Indonesia Youtube Channel. The youtube channel name is Cerdas Berkarakter Kemdikbud RI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Zou (2019), for example, expressed that, while the Internet can give additional resources, the inaccuracy and unprofessional quality of material will have an impact on children's knowledge development. Similarly, while Craig (2003) reported that using internet language improves the development of children's language, some studies have shown that using online language excessively might impair one's capacity to academic write (Dansieh, 2008;Irawaty et al, 2022).…”
Section: Mediamentioning
confidence: 99%
“…Zou (2019), for example, expressed that, while the Internet can give additional resources, the inaccuracy and unprofessional quality of material will have an impact on children's knowledge development. Similarly, while Craig (2003) reported that using internet language improves the development of children's language, some studies have shown that using online language excessively might impair one's capacity to academic write (Dansieh, 2008;Irawaty et al, 2022).…”
Section: Mediamentioning
confidence: 99%